PENGUATAN LITERASI LINGKUNGAN TENTANG TUMBUHAN YANG BERPERAN DALAM MITIGASI EROSI (LONGSOR) PADA PEMUDA DI DESA SAMBIK BANGKOL KECAMATAN GANGGA, KABUPATEN LOMBOK UTARA - Slamet Mardiyanto Rahayu; Syuhriatin, Syuhriatin (Nusantara Hasana Journal, 2024)
Sambik Bangkol is one of the villages in Gangga District, North Lombok Regency. Based on the 2021-2025 North Lombok Regency Disaster Risk Study, Sambik Bangkol is one of the villages that has the potential threat of landslides in the moderate category. Based on community service activities, it can be seen that youth in Sambik Bangkol Village, among other things: better understand the physical environmental conditions in Sambik Bangkol Village, better understand the potential for erosion (landslides) in Sambik Bangkol Village, and better understand the types of plants that have the potential to absorb water. water and reduce the potential threat of erosion (landslides) in Sambik Bangkol Village.